Histopathology of the skin - Lever, Walter F; Schaumburg-Lever, Gundula (J.B. Lippincott, 1990)
...provides succinct clinical descriptions with superb illustrations which are invaluable to residents in both dermatology and pathology.
Keywords: patologie; dermatovenerologie; Skin Diseases; kožní nemoci